Short Communication: Local perceptions about utilization of invasive alien species Opuntia ficus-indica in three Local Municipalities in the Eastern Cape Province, South Africa - LULEKA MDWESHU; A. Maroyi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Mdweshu L, Maroyi A. 2020. Short Communication: Local perceptions about utilization of invasive alien species Opuntia ficus-indica in three Local Municipalities in the Eastern Cape Province, South Africa. Biodiversitas 21: 1653-1659.  Opuntia ficus-indica is a succulent plant species categorized as invasive in South Africa but has both commercial and non-market uses. This study evaluated local people’s perceptions about utilization of O. ficus-indica in three local Municipalities in the Eastern Cape province of South Africa. Data on the local perceptions on O. ficus-indica in the study area were documented through focus group discussions and semi-structured interviews via questionnaires with households between June 2018 and August 2019. A sample of 150 participants chosen using snowball-sampling method provided information on utilization of O. ficus-indica. The importance of O. ficus-indica as a useful plant species was ubiquitously perceived, with all participants reporting its contribution as an important component of their livelihood needs and more than three quarters (88.0%) were using the species on a regular basis. Close to half of the respondents (49.3%) regarded O. ficus-indica as an important source of cash income. The positive socio-economic contributions of O. ficus-indica need to be taken into account when evaluating the costs and benefits resulting from invasions caused by alien plant species.